Problematika Pembelajaran Dengan Metode Sambil Bermain Di Raudhatul Atfal (RA) Darul Ulum Kota Sorong Tahun Pelajaran 2020/2021 - Umar Sulaiman; Widiya Ningrum (MISOOL: Jurnal Pendidikan Dasar, 2023)
This study tries to find out the problems of learning using the chili play method at Raudhatul Atfal Darul Ulum, Sorong City, for the 2020/2021 academic year. The author uses learning analysis to find problems that arise and solutions to these problems. This paper finds some of the problems faced by students and educators at RA Darul Ulum and solutions to these problems.